Optimasi Sumber Daya dan Kolaborasi Mulitpihak (Pentaheliks): Suatu Kajian Perencanaan Bahasa - Siti Hamidah (Balai Bahasa Provinsi Riau, 2023)
Indonesia as a multilingual country requires careful language planning so that language can be developed in accordance with the pace of national civilisation. The study in this article is a descriptive study with a qualitative approach. The analysis is based on the data from the literature study. Based on the descriptive results of the literature study, it is found that language planning in Indonesia has fulfilled all elements of language planning starting from planning the status of Indonesian language has the status / position as the national language and state language, languages other than Indonesian and foreign languages are regional languages, and languages in Indonesia other than Indonesian and regional languages are foreign languages. Based on these facts, Indonesia is a country that has a complexity of conditions and language problems. Therefore, optimising resources and collaborating with the pentaheliks model is a must. All elements of policy makers and the community will streamline the language planning.